A single-centre retrospective analysis of cinacalcet therapy in primary hyperparathyroidism. Issue 11 (5th November 2021) - Bell, Daniel; Hale, Julia; Go, Cara; Challis, Ben G; Das, Tilak; Fish, Brian; Casey, Ruth T
Abstract : Primary hyperparathyroidism (pHPT) is a common endocrine disorder that can be cured by parathyroidectomy; patients unsuitable for surgery can be treated with cinacalcet. Availability of surgery may be reduced during COVID-19, and cinacalcet can be used as bridging therapy. In this single-centre retrospective analysis, we investigated the utility and safety of cinacalcet in patients with pHPT receiving cinacalcet between March 2019 and July 2020, including pre-parathyroidectomy bridging. We reviewed and summarised the published literature. Cinacalcet dosages were adjusted by endocrinologists to achieve target calcium < 2.70 mmol/L. Eighty-six patients were identified, with the most achieving target calcium (79.1%) with a mean dose of 39.4 mg/day (±17.1 mg/day) for a median duration of 35 weeks (1–178 weeks). Calcium was normalised in a median time of 5 weeks. The majority of patients commenced cinacalcet of 30 mg/day (78 patients) with the remainder at 60 mg/day (8 patients). Forty-seven patients commencing lower dose cinacalcet (30 mg/day) achieved target calcium without requiring 60 mg/day. Baseline PTH was significantly higher in patients requiring higher doses of cinacalcet. 18.6% of patients reported adverse reactions and 4.7% discontinued cinacalcet. Patients treated with cinacalcet pre-parathyroidectomy required a higher dose and fewer achieved target calcium compared to medical treatment with cinacalcet alone. Post-operative calcium was similar to patients who were not given pre-parathyroidectomy cinacalcet. In summary, cinacalcet at an initial dose of 30 mg/day is safe and useful for achieving target calcium in patients with symptomatic or severe hypercalcaemia in pHPT, including those treated for pre-parathyroidectomy. We propose a PTH threshold of >30 pmol/L to initiate at a higher dose of 60 mg/day.